Colloidal solution of silver nanoparticles for label-free colorimetric sensing of ammonia in aqueous solutions - Buccolieri, Alessandro; Serra, Antonio; Giancane, Gabriele; Manno, Daniela (Beilstein Journal of Nanotechnology, 2018)
Silver nanoparticles were synthesized in the presence of saccharides and ammonia (NH3) in the concentration range from 10−2 to 103 ppm to develop an optical sensor for NH3 in aqueous solutions. Ammonia affects the features of the nanoparticles obtained in a concentration-dependent manner as determined by UV–vis absorption analysis and TEM observations. Structural and morphological analysis provides the basis for the production of a colorimetric label-free sensor for ammonia. Overall, surface plasmon resonance increases when ammonia concentration rises, although the functional trend is not the same over the entire investigated ammonia concentration range. Three different ranges have been identified: very low ammonia concentrations from 0.01 to 0.2 ppm, high ammonia concentrations from 20 to 350 ppm and, most importantly, the intermediate or physiological range of ammonia from 0.5 to 10 ppm.
Keywords: electron diffraction; electron microscopy; NH3 sensors; silver nanoparticles; UV–vis spectroscopy